2016
DOI: 10.1002/admi.201500848
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite Crystals Embedded Nanotextured Coating with Hydrophobic Surface: An Innovation Toward Next Generation Solar Cover Glass for Efficient Light‐Harvesting

Abstract: the cover glasses. Therefore, the second generation was referred to the glasses with antirefl ective (AR) coatings. However, the normal AR coatings based on optical interference design (by controlling thickness and refractive index) are thin, possess low hardness, and fail to transmit sunlight with high percentage in the wide region of wavelength (400-2000 nm). [ 7,8,11 ] Furthermore, due to the comparatively smooth surface of conventional AR coating, the less favorable fl at angle radiations of sunlight canno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…For zeolite A, T–O–T vibration mode is registered close to 489 cm −1 [34]. Small amplitude peaks at 689 cm −1 and 558 cm −1 are related to the presence of four and six-member double rings of zeolite, respectively [35].…”
Section: Resultsmentioning
confidence: 99%
“…For zeolite A, T–O–T vibration mode is registered close to 489 cm −1 [34]. Small amplitude peaks at 689 cm −1 and 558 cm −1 are related to the presence of four and six-member double rings of zeolite, respectively [35].…”
Section: Resultsmentioning
confidence: 99%
“…When NaOH concentrations of over 3 M are used, previous studies [74] have also shown the presence of hydroxy sodalite. With a decrease in degree crystallinity, higher alkalinity promotes the formation of impurities and the decomposition of zeolite [75].…”
Section: Hydrothermal Synthesis Of Zeolitementioning
confidence: 99%
“…The generation of solar power as a renewable energy source is highly important in society for a variety of applications. [1][2][3][4][5][6][7][8] In the current scenario, the development of Si solar cells or photovoltaic cells that convert direct sunlight into electric energy is drawing increasing attention because it prevents environmental pollution. Solar cell modules are normally fabricated by sandwiching an Si solar cell between a back sheet and a cover glass (front sheet) and sealing them with a resin material.…”
Section: Introductionmentioning
confidence: 99%
“…As the cover glass is exposed to open air, dust particles may adhere to it, reducing its transparency and thus decreasing the conversion efficiency of the solar cell module. [1][2][3] To maintain the conversion efficiency of the solar cell at a desirable level, the cover glass must be coated with a protective, hard and hydrophobic layer with low reflective properties. The use of mesoporous silica with a relatively ordered pore structure as a coating layer has been proven to achieve better light conversion efficiency with easy cleaning and maintenance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation